Experimental and numerical studies on super-cavitating flow of axisymmetric cavitators - Byoung-Kwon Ahn; Chang-Sup Lee; Hyoung-Tae Kim (International Journal of Naval Architecture and Ocean Engineering, 2010)
Recently underwater systems moving at high speed such as a super-cavitating torpedo have been studied for their practical advantage of the dramatic drag reduction. In this study we are focusing our attention on super-cavitating flows around axisymmetric cavitators. A numerical method based on inviscid flow is developed and the results for several shapes of the cavitator are presented. First using a potential based boundary element method, we find the shape of the cavitator yielding a sufficiently large enough cavity to surround the body. Second, numerical predictions of supercavity are validated by comparing with experimental observations carried out in a high speed cavitation tunnel at Chungnam National University (CNU CT).